Solving the Entrepreneurial Puzzle: The Role of Entrepreneurial Interpretation in Opportunity Formation and Related Processes - Barreto, Ilídio (Journal of Management Studies, 2012)
abstractOpportunity formation plays a central role in the entrepreneurship literature. The two dominant perspectives on this topic (discovery view and creation view) tended to consider search and action as the main mechanisms. Drawing on strategic issue interpretation view and managerial cognition perspective, we argue for the inclusion of a third mechanism (entrepreneurial interpretation). Specifically, we develop the boundary assumptions and testable propositions of an entrepreneurial interpretation model. Then, we show how entrepreneurial interpretation informs both discovery and creation processes. Overall, our theory provides an expanded understanding of how individuals form and decide to exploit opportunities.